1998
DOI: 10.1080/08964289809596373
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Sleep and Measures of Health and Weil-Being in College Students: A Repeated Measures Approach

Abstract: The stability of subjective measures of sleep, health, and well-being, as well as the stability of the relationships between sleep and health and well-being were assessed over 3 months. Healthy college students with no consistent sleep complaints completed a 7-day sleep log and battery of surveys related to health and well-being at 3 separate times during the 3 months. Measures of health and well-being were more strongly related to the quality than to the quantity of sleep. Further analyses using the repeated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
79
1
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 18 publications
10
79
1
4
Order By: Relevance
“…A relationship has been detected between sleep and measures of health and well-being in college students (10). Although it has been suggested that increasing sleep duration might not directly improve quality of life (11), in our study we found an improvement in the quality of sleep of the students on the late class schedule.…”
supporting
confidence: 65%
“…A relationship has been detected between sleep and measures of health and well-being in college students (10). Although it has been suggested that increasing sleep duration might not directly improve quality of life (11), in our study we found an improvement in the quality of sleep of the students on the late class schedule.…”
supporting
confidence: 65%
“…In this work, we utilize physical activity as the behavioral input due to the large body of research that supports that there is a strong relation of mental wellbeing with activity levels and sleep [17], [18], [19], [20], [21], [22], [23], [24], [25]. Further there has been a large body of work that has shown that smartphone accelerometer data can be used to sense both physical activity through activity recognition [26], [27], [28], as well as sleep [29], [30].…”
Section: Related Workmentioning
confidence: 99%
“…It is a well known fact that sleep and health are closely related [1][2][3] . In the working population, inadequate sleep could induce not only deterioration of health but could also lead to sleepiness during work which is associated with increased risk of accident at work, absenteeism, low work productivity, and less job satisfaction [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%